Competitive immobilization of Pb in an aqueous ternary-metals system by soluble phosphates with varying pH. (September 2016) - Zhang, Zhuo; Ren, Jie; Wang, Mei; Song, Xinlai; Zhang, Chao; Chen, Jiayu; Li, Fasheng; Guo, Guanlin
Abstract: Chemical immobilization by phosphates has been widely and successfully applied to treat Pb in wastewater and contaminated soils. Pb in wastewaters and soils, however, always coexists with other heavy metals and their competitive reactions with phosphates have not been quantitatively and systematically studied. In this approach, immobilization of Pb, Zn, and Cd by mono-, di-, and tripotassium phosphate (KH2 PO4, K2 HPO4, and K3 PO4 ) was observed in the single- and ternary-metals solutions. The immobilization rates of the three metals were determined by the residual concentration. The mineral composition and structure of the precipitates were characterized by powder X-ray diffraction (XRD) analysis and scanning electron microscopy (SEM). The results indicated that competitive reaction occurred in Pb-Zn-Cd ternary system, with immobilization rates decrease of <3.6%, <78%, and <89% for Pb, Zn and Cd (molar ratios of P: metal <1), respectively, compared to single metal system. The reaction of Pb with three phosphates exhibited intense competitiveness and the phosphates had a stronger affinity for Pb when Cl − was added. Pb-phosphate minerals formed by KH2 PO4 with the better crystalline characteristics and largest size were very stable with a low dissolution rate (<0.02%) in the solution of pH 2.88, compared to K2 HPO4 and K3 PO4 . This study demonstrated that Pb could be firstly and effectively immobilized by phosphates in multi-metal solutions containing Pb, Zn and Cd. Moreover, the research provided the insight of the importance of phosphate with low pH (e.g. KH2 PO4 ) and the presence of Cl − for more efficient immobilization of Pb in the multi-metals pollution system. Graphical abstract: Highlights: Precipitation of Pb, Zn and Cd by phosphates was quantitatively studied. Pb immobilization in ternary-metals solutions exhibited competitiveness. Pb-P minerals formed by KH2 PO4 and Cl − were very stable. Stability of Pb-P minerals depends on pH, mineral types, and crystallinity.